Technical Tender Evaluation Using Analytical Hierarchy Process (AHP) - Mohamed, Nor Hafizah; Lamsali, Hendrik; Sathyamoorthy, Dinesh (SCIENCE & TECHNOLOGY RESEARCH INSTITUTE FOR DEFENCE, 2017)
The selection of competent tenderers in high-value projects and procurements is very critical, as it determines the risks and outcomes of the projects. In some government procurement systems, millions of dollars are at stakes. Unfortunately, a significant number of high-value projects and procurements have failed to achieve the intended goals and standards due to incompetent tenderers. Hence, employing the right decision making approach in the tender evaluation and selection process is vital. This study evaluates the use of analytical hierarchy process (AHP) for technical tender evaluation using a case study. The findings show that AHP is more effective than the present method which employs the scoring and weighted sum model. AHP also provides more accurate results with minimal bias. It is expected that the findings of this study will be beneficial to improve the existing procurement system. In general, the findings may also be applicable and beneficial to other highvalue government procurement systems